A saliency mapping approach to understanding the visual impact of wind and solar infrastructure in amenity landscapes. Issue 2 (4th March 2023) - Mohammadi, Mehrnoosh; Chen, Yan; Rahman, H. M. Tuihedur; Sherren, Kate
ABSTRACT: Shifts from fossil fuels toward renewable energy (RE) introduce profound changes to landscapes, including visual impacts that are often investigated during environmental and social impact assessment. Moreover, RE transitions are among many visual changes happening in rural areas that are increasingly serving amenity functions and becoming destinations for wide ranges of users. This diversity introduces complexities during infrastructure siting discussions. Emerging grape and wine production landscapes in Canada serve amenity and production purposes, and this study was designed to understand the impacts of RE development using case studies of solar panels and wind turbines in two vineyard landscapes in Ontario (ON) and British Columbia (BC). We applied novel mixed methods, including content analysis and saliency-based visual impact analysis, to textual and image-based representations posted on Instagram of those vineyards. In this case, the addition of low-density RE infrastructures did not seem to disturb the vineyard experience. The technique presented can be applied in a wide range of infrastructure siting contexts, both before and after construction, but requires additional research and calibration.